Artificial refuges for wildlife conservation: what is the state of the science?. (16th July 2021) - Cowan, Mitchell A.; Callan, Michael N.; Watson, Maggie J.; Watson, David M.; Doherty, Tim S.; Michael, Damian R.; Dunlop, Judy A.; Turner, James M.; Moore, Harry A.; Watchorn, Darcy J.; Nimmo, Dale G.
ABSTRACT: Artificial refuges are human‐made structures that aim to create safe places for animals to breed, hibernate, or take shelter in lieu of natural refuges. Artificial refuges are used across the globe to mitigate the impacts of a variety of threats on wildlife, such as habitat loss and degradation. However, there is little understanding of the science underpinning artificial refuges, and what comprises best practice for artificial refuge design and implementation for wildlife conservation. We address this gap by undertaking a systematic review of the current state of artificial refuge research for the conservation of wildlife. We identified 224 studies of artificial refuges being implemented in the field to conserve wildlife species. The current literature on artificial refuges is dominated by studies of arboreal species, primarily birds and bats. Threatening processes addressed by artificial refuges were biological resource use (26%), invasive or problematic species (20%), and agriculture (15%), yet few studies examined artificial refuges specifically for threatened (Vulnerable, Endangered, or Critically Endangered) species (7%). Studies often reported the characteristics of artificial refuges (i.e. refuge size, construction materials; 87%) and surrounding vegetation (35%), but fewer studies measured the thermal properties of artificial refuges (18%), predator activity (17%), or food availability (3%). Almost all studies measured occupancy of the artificial refuges by target species (98%), and over half measured breeding activity (54%), whereas fewer included more detailed measures of fitness, such as breeding productivity (34%) or animal body condition (4%). Evaluating the benefits and impacts of artificial refuges requires sound experimental design, but only 39% of studies compared artificial refuges to experimental controls, and only 10% of studies used a before‐after‐control‐impact (BACI) design. As a consequence, few studies of artificial refuges can determine their overall effect on individuals or populations. We outline a series of key steps in the design, implementation, and monitoring of artificial refuges that are required to avoid perverse outcomes and maximise the chances of achieving conservation objectives. This review highlights a clear need for increased rigour in studies of artificial refuges if they are to play an important role in wildlife conservation.